WSe2/2D electron gas heterojunction on KTaO3 for room-temperature giant photoconductivity. Issue 6 (15th March 2021) - Zhou, Ze; Huang, Gensheng; Shen, Jiaxin; Gong, Shuainan; Zhou, Pengfei; Yin, Lingyu; Zhao, Run; Liu, Guozhen; Zhang, Jinlei; Li, Yang; Ma, Chunlan; Jiang, Yucheng
Abstract: Van der Waals (vdW) heterojunctions, based on 2D systems, show great potential as high-performance photodetectors. Recent advances have reported an Ar + -ion-bombardment assistant method to achieve a vdW heterojunction between a 2D-material and a 2D electron gas (2DEG). Here, we fabricate a vdW heterojunction between WSe2 and 2DEG on KTaO3 . Under visible light illumination, a giant photoconductivity is observed with bias voltage applied at room temperature. Such a device exhibits an instantaneous photoelectric response to on/off light illumination. The ratio of on/off currents reaches as high as 10 4 . In the wavelength range of 405–808 nm, the photoresponsivity is much greater for shorter wavelengths, reaching a maximum of 1.84 A/W. Moreover, even without bias voltage, the WSe2 /2DEG heterojunction still generates a short-circuit photocurrent due to the photovoltaic effect, implying a self-powered photodetector. This work paves a path towards high-performance photoelectric devices based on vdW heterojunctions of 2D-material/2DEG.